2009
DOI: 10.1108/09590550910988039
|View full text |Cite
|
Sign up to set email alerts
|

Testing a MIMIC model of e‐shopping site usage

Abstract: PurposeThe purpose of this paper is to develop a multiple‐indicator‐multiple‐cause (MIMIC) model that assesses the relative influence of various e‐shopping web site design attributes on e‐shopping web site usage intention.Design/methodology/approachData from a survey of 261 students are used to test the research model. Factor analysis is performed to ascertain distinct constructs. LISREL analysis of the survey data is then used to test the proposed MIMIC model.FindingsThe results showed the effect of the dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…) According to the literature on MIMIC models (e.g. Lim, Heinrichs and Lim, 2009;Safón, 2009), we introduce an additional hypothesis to test whether our approximation meets the statistical requirements for measurement models.…”
Section: H1mentioning
confidence: 99%
“…) According to the literature on MIMIC models (e.g. Lim, Heinrichs and Lim, 2009;Safón, 2009), we introduce an additional hypothesis to test whether our approximation meets the statistical requirements for measurement models.…”
Section: H1mentioning
confidence: 99%
“…In online financial services, such system functions as product variety, service process, and service quality were found to affect the flow experience, which, in turn, influenced customer satisfaction with the service (Ding et al , 2010). Lim et al (2009) found that web site attributes promoting the feeling of participation (playfulness) increase an e‐shopper's intentions to continue buying from the web site. Additionally, Ballantine (2005) found that a web site's interactivity increases visitors' satisfaction.…”
Section: Components Of E‐tail Customer Experience: Exploratory Phase and Hypotheses Formulationmentioning
confidence: 99%
“…In the context of the online environment, high IQ is likely to help users to research and compare online products (e.g., books, music CDs, electronic goods) and services (e.g., health information, consumer banking and finance), and to consequently be able to make better online decisions. Thus, perceiving high online IQ increases consumers' satisfaction and may help them to perceive websites as being more useful in accomplishing their tasks [22,71,94].…”
Section: Introductionmentioning
confidence: 99%